Absent presences in the colonial archive: dealing with the Berlin Sound Archive's acoustic legacies. - Hilden, Irene (Leuven University Press, 2022)
The Berlin Sound Archive (Lautarchiv) consists of an extensive collection of sound recordings, compiled for scientific purposes in the first half of the 20th century. Recorded on shellac are stories and songs, personal testimonies and poems, glossaries and numbers. This book engages with the archive by consistently focusing on recordings produced under colonial conditions.With a firm commitment to postcolonial scholarship, Absent Presences in the Colonial Archive is a historical ethnography of a metropolitan institution that participated in the production and preservation of colonial structures of power and knowledge. The book examines sound objects and listening practices that render the coloniality of knowledge fragile and inconsistent, revealing the absent presences of colonial subjects who are given little or no place in established national narratives and collective memories.